Getting the Full Picture in English and Spanish? Audio Described Characters in Netflix’s Élite - García Vizcaíno, María José (Journal of Audiovisual Translation, 2021)
Drawing on the mental model theory of fictional characters (Schneider, 2001) applied to audio description (Fresno, 2016), this paper examines the audio description (AD) of characters in English and Spanish for the Netflix series Élite. The study is based on the premise that semantic descriptions of characters, rather than merely visual descriptions of physical traits, contribute to a better understanding of the narrative complexities of a film, favour AD users’ memory, and reduce cognitive effort (Fresno et al., 2016). This contrastive analysis shows how pertinent description of action movements and appearances together with lexical accuracy can trigger helpful semantic meanings that reveal characters’ psychological features. Because Élite is a thriller in which the majority of the characters are murder suspects, accessing all types of information about them is essential to fully understand the plot. In addition, this analysis indicates that the English AD emphasizes certain character attributes which are absent from the Spanish AD, a distinction that influences the semantic domains, filmic cohesion and coherence of the narrative. This finding underscores the fact that cross-linguistic and cultural differences actually affect the reception of a fictional character by AD users (Orero, 2008; Mazur & Chmiel, 2012) and consequently, their appreciation and enjoyment of the program in question. Lay summary This paper examines the audio description (AD) of characters in English and Spanish for the Netflix series Élite. Based on previous studies (Fresno, 2014; Fresno, 2016), this analysis shows that not only physical traits, but also the description of action movements and looks can trigger helpful semantic inferences that reveal crucial characters’ psychological features. Because Élite is a thriller in which most of the characters are murder suspects, grasping all types of information about them is essential to fully understand the plot. In addition, this paper indicates that the English AD emphasizes certain character attributes which are absent in the Spanish AD. This finding underscores the fact that cross-linguistic and cultural differences actually affect the reception of a fictional character by AD users (Orero, 2008; Mazur & Chmiel, 2012) and consequently, their appreciation and enjoyment of the show in question.